Estimation of Electric Power Economy while Using Anti-Turbulent Additives in Oil Pipeline - V. A. Anischenko; N. V. Tokochakova; А. S. Fikov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper contains a method for estimation of electric power economy due to addition of anti-turbulent additives while transporting oil. The proposed method is based on a statistic model constructed according to daily statistics that reflects the established power consumption regimes at an enterprise. A nomograph is developed on the basis of the model using an elasticity factor. The nomograph significantly simplifies engineering calculations.